2014
DOI: 10.1038/ja.2014.100
|View full text |Cite
|
Sign up to set email alerts
|

Bafilomycin L, a new inhibitor of cholesteryl ester synthesis in mammalian cells, produced by marine-derived Streptomyces sp. OPMA00072

Abstract: Marine-derived Streptomyces sp. OPMA00072 was found to produce inhibitors of the synthesis of neutral lipids in a cell-based assay using Chinese hamster ovary (CHO) cells. A new 16-membered macrolide named bafilomycin L (BFL) (1) was isolated along with the known structurally related bafilomycin C1 (BFC1) (3) from the culture broth of the actinomycete by solvent extraction, octadecylsilyl column chromatography and HPLC. BFL inhibited cholesteryl ester (CE) synthesis in CHO cells with an IC50 value of 0.83 nM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…DNA extraction, PCR, sequencing and Basic Local Alignment Search Tool searching followed. 16,17 The primer set ITS-5 (5′-GGAAGTAAAAGTCGTAACAAGG-3′) and NL-4 (5′-GGTCCGTGTTTCAAGACGG-3′) was used to amplify the region under the conditions of 30 cycles at 94°C for 30 s, 60°C for 30 s and 72°C for 90 s. The sequence is available at the DNA Data Bank of Japan/European Molecular Biology Laboratory/GenBank databases under the accession number AB934385. On the basis of the Basic Local Alignment Search Tool search and its microscopic features, the strain was identified as a Graphium sp.…”
Section: Collection and Identification Of Strain Opmf00224mentioning
confidence: 99%
“…DNA extraction, PCR, sequencing and Basic Local Alignment Search Tool searching followed. 16,17 The primer set ITS-5 (5′-GGAAGTAAAAGTCGTAACAAGG-3′) and NL-4 (5′-GGTCCGTGTTTCAAGACGG-3′) was used to amplify the region under the conditions of 30 cycles at 94°C for 30 s, 60°C for 30 s and 72°C for 90 s. The sequence is available at the DNA Data Bank of Japan/European Molecular Biology Laboratory/GenBank databases under the accession number AB934385. On the basis of the Basic Local Alignment Search Tool search and its microscopic features, the strain was identified as a Graphium sp.…”
Section: Collection and Identification Of Strain Opmf00224mentioning
confidence: 99%
“…isolated from litter at a river mouth. 60 Following genetic manipulation of a marine Streptomyces olivaceus by disruption of orf-1741, a putative transcriptional gene, three halogenated dibenzoxazapinone derivatives, the mycemycins C-E 62-64, were isolated from the mutant strain and are the rst dibenzoxazapinones produced from a microbial source. 61 Marine Actinobacteria continue to surprise with the versatility of their biosynthetic machinery.…”
Section: Introductionmentioning
confidence: 99%
“…However, while bafilomycin B 1 and bafilomycin C 1 have antibacterial activity, bafilomycin A 1 displays no detectable antibacterial activity [2]. Similarly, a recent report found that bafilomycin L, which does not contain a fumarate moiety, has no antibiotic activity [6]. These observations lead us to speculate that the fumarate might contribute to antibacterial activity and we thus determined the minimum inhibitory concentration (MIC) of JBIR-100 against a number of bacteria.…”
Section: Resultsmentioning
confidence: 95%